2019
DOI: 10.1021/acs.energyfuels.9b01222
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Adding Asphaltenes and Gas Condensate on CO2 Hydrate Formation in Water–CO2–Oil Systems

Abstract: Gas hydrate formation is a huge flow assurance problem in offshore production of oil and gas. However, there have been some reported cases in oil-dominated systems where the hydrates do not form, even though the high-pressure and low-temperature environments induce favorable thermodynamic conditions. The reason for this unexpected result seems to be related to the presence of natural chemical compounds in crude oils that prevent the hydrates’ nucleation and agglomeration. Because the number of works in this sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 54 publications
1
17
1
Order By: Relevance
“…It is quite different from Sandoval’s conclusion, whose experimental mass fraction of powder asphaltene ranged from 0.0874 to 2.8 wt %. Furthermore, asphaltene exists in a dissolved phase in this work compared with the particulate phase.…”
Section: Resultscontrasting
confidence: 93%
See 2 more Smart Citations
“…It is quite different from Sandoval’s conclusion, whose experimental mass fraction of powder asphaltene ranged from 0.0874 to 2.8 wt %. Furthermore, asphaltene exists in a dissolved phase in this work compared with the particulate phase.…”
Section: Resultscontrasting
confidence: 93%
“…Stoporev utilized an autoclave to test the hydrate formation kinetics of water-in-oil emulsion and also found that the oil–water system containing asphaltenes could decelerate the nucleation rate and increase the induction time. This conclusion is consistent with that of Sandoval, who determined the positive correlation between the amount of asphaltenes and the induction time when investigating the effect of powder asphaltene on carbon dioxide hydrate formation. Morrissy used the micromechanical force (MMF) apparatus to explore the growth rate of cyclopentane hydrate films and proposed that natural surface activity components in oil may be adsorbed on the water–cyclopentane interface, which destroys the assembly of hydrate crystals, exhibiting a palpable decrease in the growth rate of hydrate films.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…This happens due to the arrangement and solubility of asphaltenes at the interface or hindering of the guest−host interaction, 40 or both. 41 On the contrary, there are studies that have reported a decrease in the hydrate inhibition tendency with increased asphaltene content or even promotion. For example, the authors observed an increase in agglomeration and a decrease in supercooling with an increase in the asphaltene content in the system.…”
Section: Introductionmentioning
confidence: 98%
“…Asphaltene has been shown to increase hydrate induction and growth time in water–CO 2 –oil systems but does not avoid hydrate formation, typically working as a kinetic hydrate inhibitor (KHI). This happens due to the arrangement and solubility of asphaltenes at the interface or hindering of the guest–host interaction, or both . On the contrary, there are studies that have reported a decrease in the hydrate inhibition tendency with increased asphaltene content or even promotion.…”
Section: Introductionmentioning
confidence: 99%